From economic difficulties to psychological maladjustment in Italian women during the Covid-19 pandemic: does marital dissatisfaction moderate or mediate this association? - Camisasca, Elena; Covelli, Venusia; Cafagna, Dario; Manzoni, Gian Mauro; Cantoia, Manuela; Bavagnoli, Alessandra; Crescenzo, Pietro; Marsicovetere, Vincenzo; Pesce, Mario; Visco, Marina Angela (Frontiers in Psychology, 2023)
Introduction The empirical study about the negative impact of economic difficulties due to Covid- 19 on the psychological well-being of Italian women by considering perceived stress and marital satisfaction is an area worthy of investigation. The study explored these variables by hypothesizing that marital satisfaction (DAS) could moderate or mediate the links between economic difficulties, perceived stress (PSS), and psychological maladjustment (PGWBI). Methods A total of 320 Italian women completed an online survey about the study’s variables during the lockdown period. Women’s perceptions of economic difficulties due to COVID- 19 restrictions were detected through an ad-hoc specific question. Perceived stress, marital satisfaction and psychological maladjustment were assessed by standardized questionnaires (Perceived Stress Scale 10, Dyadic Satisfaction Scale and Psychological General Well-being Inventory). Results 39.7% of women who answered the online survey said that the Covid-19 significantly impacted their family income. Results indicated that marital satisfaction did not moderate the associations investigated. Conversely, data showed how economic difficulties (X) predicted lower psychological maladjustment through the mediation of perceived Stress (M1), which, in turn, was associated with higher levels of marital dissatisfaction (M2). Conclusion The results of the present study confirm the significant role of marital dissatisfaction in explaining the indirect effects of economic difficulties on psychological maladjustment in women. In particular, they indicated a significant spillover effect which transmitted strains experienced in one domain (economic difficulties) to another (the dissatisfaction of the couple), which in turn affected the psychological maladjustment.